X-ray absorption spectroscopy analysis of the effect of MnO2doping on local structure of ((K0.5Na0.5)0.935Li0.065)NbO3ceramics - Kanokwan Kanchiang (2018)
In this work, the extend X-ray absorption fine structure (EXAFS) analysis was performed in combination with the density functional theory (DFT) calculation to investigate local structure of Mn-doped ((K0.5Na0.5)0.935Li0.065)NbO3. From the structural relaxation, Mn3+is substituted on Nb5+to produce oxygen vacancy in the longest bond length in c-axis. Further, from the EXAFS Fourier transform comparison in R-space, the bond lengths between Mn3+and O2-are almost equal in both ab-and c-axis with increasing Mn-doping contents. This is strong evidence that Mn-doping played an important role in producing the polarization domains in opposite direction, which diminish remnant polarization, pinning the domains wall movement and increase coercive field. © 2014 Taylor & Francis Group, LLC.